Hubungan Kadar Ureum terhadap Restless Legs Syndrome pada Pasien Chronic Kidney Disease - Gusri Rahayu; Hema Malini; Elvi Oktarina (Universitas Andalas, 2019)
Abstract              Chronic Kidney Disease (CKD) is a condition where the body fails to maintain metabolism and fluid and electrolyte balance to cause uremia. Chronic Kidney Disease requires renal replacement therapy in the form of dialysis and kidney transplantation. Long-term hemodialysis and uremia can cause various neurological complications such as Restless Legs Syndrome (RLS). This study is a correlation analysis using a cross sectional study design with a sampling technique that is purposive sampling of 16 hemodialysis patients. Data were analyzed using pearson correlation test. The results showed that there was a correlation between urea level and severity of Restless Legs Syndrome in Chronic Kidney Disease patients with p value (0,028). There is a need for training and monitoring of urea levels in an effort to improve the severity of RLS.   Keywords: Chronic Kidney Disease;Restless Legs Syndrome;Ureum Levels.   Abstrak Chronic Kidney Disease (CKD) merupakan kondisi dimana tubuh gagal dalam mempertahankan metabolisme serta keseimbangan cairan dan elektrolit hingga menyebabkan uremia. Chronic Kidney Disease membutuhkan renal replacement therapy berupa dialysis dan transplantasi ginjal. Hemodialisis dalam jangka waktu yang lama dan uremia dapat menimbulkan berbagai komplikasi neurologi seperti Restless Legs Syndrome (RLS). Penelitian ini adalah analisis korelasi menggunakan  desain penelitian cross sectional dengan teknik pengambilan sampel yaitu purposive sampling sebanyak 16 pasien hemodialisis. Data dianalisis menggunakan uji korelasi pearson. Hasil penelitian menunjukkan terdapat hubungan kadar ureum terhadap keparahan Restless Legs Syndrome pada pasien Chronic Kidney Disease dengan nilai p value (0,028). Perlu adanya latihan atau exercise serta pemantauan kadar ureum dalam upaya memperbaiki keparahan RLS.   Kata kunci:  Chronic Kidney Disease;Restless Legs Syndrome;Ureum Levels.